2019
DOI: 10.1051/0004-6361/201834318
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation of chemical abundances derived using IR spectra obtained with GIANO

Abstract: Context. Detailed chemical abundances of Galactic stars are needed in order to improve our knowledge of the formation and evolution of our galaxy, the Milky Way. Aims. We took advantage of the GIANO archive spectra to select a sample of Galactic disc stars in order to derive their chemical inventory and to compare the abundances we derived from these infrared spectra to the chemical pattern derived from optical spectra. Methods. We analysed high-quality spectra of 40 stars observed with GIANO. We derived the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 51 publications
3
28
6
Order By: Relevance
“…The lack of systematic offsets in abundances between optical and NIR spectra (Fig. 4) for the species under consideration here is also evident from the solar spectrum analysis, and corroborates previous results by Caffau et al (2019), who reported a systematic investigation based on 40 stars (see that paper for details).…”
Section: Resultssupporting
confidence: 91%
“…The lack of systematic offsets in abundances between optical and NIR spectra (Fig. 4) for the species under consideration here is also evident from the solar spectrum analysis, and corroborates previous results by Caffau et al (2019), who reported a systematic investigation based on 40 stars (see that paper for details).…”
Section: Resultssupporting
confidence: 91%
“…The agreement between the optical and NIR abundances for the stars is overall good, within the uncertainties. Our results corroborate the previous findings of Caffau et al (2019) by analysing spectra from GIANO in its previous configuration (fibre-fed). However, we noted that for the star HIP 61205 we obtained larger discrepancies for Mg, Si and Ni between the optical and NIR abundance; the latter values are nearly solar.…”
Section: Stellar Parameters and Elemental Abundancessupporting
confidence: 92%
“…We also note inconsistencies at the high metallicity end, in particular our measurement of the Hyades open cluster and the previous abundance measurements from Caffau et al (2011);Maas et al (2017); Caffau et al (2019) lie above the chemical evolution model. Adjustments to the chemical evolution model, an additional production may be needed, or adjustments to the metallicity dependence of supernovae yields may be needed to match [P/Fe] ratios at solar metallicity, as shown in Fig.…”
Section: P Abundances Vs T Effcontrasting
confidence: 66%
“…Targeted surveys with the Y-band P I features have confirmed an offset between chemical evolution models and abundance measurements over the -0.6 < [Fe/H] < 0.2 metallicity range (Caffau et al 2016;Maas et al 2017;Caffau et al 2019). Additional P abundances have also been measured in individual metal poor stars (Spite et al 2017) further constraining P production in the early Universe.…”
Section: Introductionmentioning
confidence: 91%